Project management : absolute beginner's guide - Horine, Greg (Que, 2017)
"Succeed as a project manager, even if you've never run a project before! This book is the fastest way to master every project management task, from upfront budgeting and scheduling through execution, managing teams through closing projects, and learning from experience. Updated with more insights from the front lines, including agile approaches, dealing with security and privacy priorities, and leading remote/virtual teams, along with the latest on Microsoft Project and PMI standards and certifications and a special bonus chapter on preparing for the PMP certification. This book will show you exactly how to get the job done, one incredibly clear and easy step at a time. Project management has never, ever been this simple! Who knew how simple project management could be? This is today's best beginner's guide to modern project management...simple, practical instructions for succeeding with every task you'll need to perform!"